DeBanda and its multiples: places, spaces, simultaneity and concurrency (Urdimento: Revista de Estudos em Artes Cênicas, 2021)
The purpose of this article is to discuss facets that make up the path of the popular musical spectacle DeBanda, aiming to unveil aspects of its complexity. To this end, multiples were considered regarding the meanings and versions that involve the aforementioned aesthetic experience, which contain: memories from recent to the most distant, places, spaces, simultaneities and concurrencies. Etymological and denotative paths, as well as popular imagination, permeate the first section. The writing continues with tour, formats, sounds, audience, passers-by, Junkers, technologies and misadventure as a modus operandi. These multiples support the reflections that range from the laboratory to seven countries in the five years of DeBanda's wanderings.
Keywords: Popular musical theater; Multiples; Spaces; Simultaneity; Concurrency